Copepods (Cyclopoida) associated with top shells (Vestigastropoda: Trochoidea: Tegulidae) from coastal waters in southern Japan, with descriptions of three new species - Uyeno, Daisuke (Zootaxa, 2016)
Four species of copepods are described based on specimens of both sexes from tegulid top shells (Vestigastropoda) caught from coastal waters of southern Japan. Three species, including two undescribed and one known of the genus Panaietis (Copepoda: Cyclopoida: Anthessiidae) were found in the pharynx and esophagus of gastropods. Panaietis incamerata Stebbing, 1900, P. doraconis n. sp., and P. satsuma n. sp. are distinguished from its congeners by the dorsal plates on the first pedigerous somite, the genital somite, the shape of the spines on legs, the number of setae on legs 1 and 2, and the position and shape of leg 5. Pseudanthessius imo n. sp. (Cyclopoida: Pseudanthessiidae) was found in the mantle cavity of the host. This copepod differs from its congeners in the proportions of the caudal ramus, the armature and proportion of the antenna, the armature of the exopod and general shape of the endopod of leg 4, and the presence of a post-rostral process.